Effect of gases released during solidification of castings on microstructure of alloys - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия, 2020)
Thermodynamic calculation of formation of spherical gas bubbles different in water – wetting on flat surfaces by metal melt is made. This process consists of two stages. The first stage is formation of equilibrium gas bubble in the form of ball segment. The second stage is its swinging into a spherical bubble. Calculations were made for gas bubbles with constant volume. It is shown that Gibbs energy of spherical gas bubble formation on water – wetting metal melt substrate is three times less than on nonwettable melt substrate. Thus, gases released by solidification of the castings will preferably be formed and removed as bubbles on the molten metal surfaces of the crystallizable phases of the alloys and directly affect on their microstructure.